1999
DOI: 10.1038/4553
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of axonal transport is a very early event in the toxicity of ALS–linked SOD1 mutants to motor neurons

Abstract: Mutations in copper/zinc superoxide dismutase 1 (SOD1), primary causes of human amyotrophic lateral sclerosis (ALS), provoke motor neuron death through an unidentified toxic property. The known neurofilament-dependent slowing of axonal transport, combined with the prominent misaccumulation of neurofilaments in ALS, suggests that an important aspect of toxicity may arise from damage to transport. Here we verify this hypothesis for two SOD1 mutations linked to familial ALS. Reduced transport of selective cargoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
353
0
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(369 citation statements)
references
References 41 publications
10
353
0
6
Order By: Relevance
“…As ALS disease progresses, so does muscular ARE activation (Figures 1 and 2), presumably because of increasing free radical deposition as the mutant SOD-induced defects are magnified and overrun endogenous defenses. It is plausible that this stress is occurring in response to a decrease in trophic factor secretion to the hindlimb from sub-lethally-damaged motor neurons, as early defects in axonal transport caused by SOD mutations have previously been shown [ (Kennel et al 1996;Williamson and Cleveland 1999)]. …”
Section: Discussionmentioning
confidence: 99%
“…As ALS disease progresses, so does muscular ARE activation (Figures 1 and 2), presumably because of increasing free radical deposition as the mutant SOD-induced defects are magnified and overrun endogenous defenses. It is plausible that this stress is occurring in response to a decrease in trophic factor secretion to the hindlimb from sub-lethally-damaged motor neurons, as early defects in axonal transport caused by SOD mutations have previously been shown [ (Kennel et al 1996;Williamson and Cleveland 1999)]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pulse exposure to Al maltolate blocks fast axonal transport leading to the accumulation of NF-L proteins in rat cortical neurons (Kashiwagi et al, 1998). Disrupted transport has been shown in AD (Cash et al, 2003;Praprotnik et al, 1996;Richard et al, 1989;Terry, 1996) and also amyotrophic lateral sclerosis (Williamson and Cleveland, 1999), however relatively few studies have examined this aspect of the disease (Kasa et al, 2000). Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport.…”
Section: Discussionmentioning
confidence: 99%
“…Although a common mechanism has not been identified, defects in axonal transport have long been implicated in this process 1 . Transgenic mice with mutant superoxide dismutase-1 show deficits in slow axonal transport early in the disease course 2 , and an early upregulation of the kinesin superfamily motor protein KIF1A was detected in spinal motor neurons 3 . In a cell model of spinal bulbar muscular atrophy, a motor neuron disease caused by a polyglutamine repeat expansion, cytoplasmic aggregates alter axonal trafficking 4 .…”
mentioning
confidence: 99%